Repurposing Individualized Nutritional Intervention as a Therapeutic Component to Prevent the Adverse Effects of Radiotherapy in Patients With Cervical Cancer - Medina-Jiménez, Ana Karen; Monroy-Torres, Rebeca (Frontiers in Oncology, 2020)
Worldwide, cervical cancer was the fourth leading cause of cancer death among women, while in Mexico was the second cause (5.28%). Cancer patients receiving chemotherapy and radiotherapy have a high risk of malnutrition secondary to the disease and treatment, affects the patient's overall, with adverse effects on gastrointestinal symptoms. These use affects the medical therapy. The aim of the present study was to evaluate the benefits on individualized nutritional therapy on decrease weight loss and gastrointestinal adverse effects and to consider these outcomes in pharmacology research, especially in repurposing drugs. We conducted a longitudinal design with two comparation groups with medical diagnosis of cervical cancer and received radiotherapy weekly, 1) the intervention group (nutritional intervention and counseling -INC-) with 20 participants and 2) control group (retrospective cohort -CG-) with 9 participants. Weekly body composition, dietary intake, adverse effects (gastrointestinal symptoms), glucose, hemoglobin, and blood pressure were analyzed during 4 to 5 weeks. Both groups had weight loss weekly (p = 0.013 and p = 0.043 respectively) but the CG vs INC presented loss fat-free mass ≥500g in 67% and of 37% respectively. By the end of the intervention a 25% of the INC group had <10 g / dL of hemoglobin vs 60% for the CG. To compare the dietary intake of vitamins (A and folic acid), fiber (p = 0.006), iron (p = 0.03) and energy (mainly carbohydrates) (p = 0.04) were according to the recommendations in INC group (p>0.05). The number needed to treat was 4 (95% CI, 2 to 13). The nutritional intervention and counseling weekly during radiotherapy in cervical cancer to maintain/improve muscle mass, hemoglobin, and dietary intake above 70% of the recommendations for INC group compared to the evidence. Adequate nutritional status was maintained and decrease the rate of complications, mainly gastrointestinal symptoms, in INC group. The efficacy of drug repurposing can improve through individualized nutritional therapy for preventing adverse effects of radiotherapy in patients with cervical cancer.